Economic ideas, capital logic and class struggle: reflections towards a people’s history of economics - Schmidt, Ingo (Society Register, 2022)
This article outlines ideas about a people’s history of economics. The goal of such a history is to use economic theory to understand the formation of classes, political projects and historical blocs and history as a history of class struggles instead of the unfolding of economic laws. The article discusses the shortcomings of existing histories of economic thought and peoples’ histories. It suggests a synthesis that offers insights into the production and diffusion of economic ideas and their role in the making and remaking of class- and state relations from industrial capitalism to the present. The last part of the article offers an outline organized around the ideas of Smith, Marx, the Marginalists, Keynes and Hayek. Though using the common big names as entry points to class- and state-formation during different periods of capitalist and imperialist development, the peoples’ history is mainly concerned with the lives, thoughts and struggles of the toiling, primarily invisible, hands performing paid and unpaid work in capitalist centres and peripheries.